Fimbrial dermoid cyst with elevated CA19-9 levels: A case report - Dan Hay; Bivas Biswas; Jaydip Dasgupta (Elsevier, 2019)
We report the case of a 39-year-old woman who presented in an acute setting with pelvic pain, an adnexal mass on imaging and a high CA19-9 level. She was taken for surgery, where a large dermoid cyst was found at the fimbrial end of a fallopian tube at the time of laparoscopy, with no apparent connection to either ovary and absence of ovarian necrosis. This was corroborated on final histology. Dermoid cysts in aberrant locations are usually reported at Caesarean section or during laparoscopic sterilisation and thus, understandably, a pre-operative CA19-9 level is rarely available. That and the rarity of these 'ectopic dermoids' make it hard to give further support for a causative association with the high tumour marker levels. Some authors suggest that auto-amputation of a dermoid cyst or part thereof and subsequent reimplantation may give rise to this phenomenon, and thus the term 'wandering dermoid' has been applied to similar situations. This is what we postulated as the cause in our case. It is likely that a full understanding of the aetiology of wandering dermoid cysts will remain elusive, given the paucity of cases. Keywords: Fimbrial, Dermoid cyst, Raised CA19-9